The Effect of The Implementation of Project Based Learning (PjBL) Model on Science Learning Outcomes of The 8th Grader (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of the application of the Project Based Learning model on the learning outcomes of the 8th grader at SMP Negeri 32 Padang on the digestive system and respiratory system. This type of research is a Quasi Experiment with a research design that is Nonequivalent Control Group Design. The population of the study covers all of the 8th grader at SMP Negeri 32 Padang which consists of 7 classes. The samples in this study were class VIII.6 as the control class and VIII.7 as the experimental class. The sampling technique used is Purposive Sampling. The instrument of this research is a Pre test – Post test question in the form of objective questions as many as 20 questions. The data that has been obtained is then analyzed using prerequisite tests, namely normality test and homogeneity test, then hypothesis testing is carried out. Based on the hypothesis test that has been carried out, the results of hypothesis testing calculations were obtained with the help of Microsoft excel using the t test technique with a significant level of 5%. The tcount ≥ ttable value is 2.56 ≥ 2.00, meaning that H0 is rejected and H1 is accepted. So, it can be concluded that the implementation of the Project Based Learning learning model has a significant effect on student learning outcomes at SMP Negeri 32 Padang